Carotid Stent Placement: State-of-the-Art - Alexander, Walter (MD Conference Express, 2006)
When the carotid artery becomes occluded by atherosclerotic plaques such that a narrowing, or stenosis, is observed, a patient is diagnosed with carotid artery disease. Carotid artery stenosis (CAS) can lead to many neurological conditions including dizziness, numbness, confusion and ultimately stroke. Whether to remove the stenoic plaque surgically, or use a carotid stent has been widely debated, and this article discusses the safety of carotid stents and when they should be used.